Infiltrative patterns of glioblastoma: identification of tumor progress using apparent diffusion coefficient histograms - Lutz, Kira; Wiestler, Benedikt; Graf, Markus; Bäumer, Philipp; Floca, Ralf; Schlemmer, Heinz-Peter; Heiland, Sabine; Wick, Wolfgang; Bendszus, Martin; Radbruch, Alexander (Journal of magnetic resonance imaging, 2014)
Purpose To investigate whether apparent diffusion coefficient (ADC) histogram analysis can differentiate between patients presenting T2-progress and patients presenting stable T2-signal in glioblastoma. Materials and Methods Fourteen patients presenting an isolated T2-progress and a matched control group exhibiting stable disease were included. Relative ADC value distribution within tumoral and peritumoral FLAIR hyperintensities were evaluated using ADC-histogram analysis. Severity and frequency of ADC shift between baseline, T2-progress, and subsequent T1-progress were analyzed using the Wilcoxon test. Results The shift of ADC histograms either to higher or to lower values in case of T2-progress was significantly more severe than in the control group (P value 0.05). Furthermore, a significant shift toward lower ADC values (P value 0.02) was detected when comparing ADC histograms of patients with T2-progress and subsequent T1-progress. Conclusion The basis for the observed ADC shift in isolated T2-progress may be time dependent: Initially, formation of peritumoral edema may cause an increase of ADC values that is followed by tumor cells infiltrating the surrounding tissue, causing a subsequent decrease of ADC values. The shift toward lower ADC values in case of subsequent T1-progress confirms this hypothesis and provides further evidence for T2-progress being an intermediate step between stable disease (SD) and T1-progress. J. Magn. Reson. Imaging 2014;39:1096-1103. © 2013 Wiley Periodicals, Inc.
Gesehen am 15.09.2020
First published: 30 September 2013